Herbicides in tropical soils and water - Ayanaba, A. (1978)
In the U. K., the amount of herbicides used on about 4.15 million hectares of agricultural land in 1973 was considered enough to provide 30 ppm if mixed evenly into the top 0.5em of the treated area (Greaves et al., 1976). How soon quantities of this kind will be used in the topics is not known. It is the responsibility of agriculturalists to maintain the productivity of the soil, and one aspect of this task is to ensure that levels of herbicides in soils and water are kept _low.